2022
DOI: 10.1016/j.paid.2021.111245
|View full text |Cite
|
Sign up to set email alerts
|

Linking the behavioral immune system to COVID-19 vaccination intention: The mediating role of the need for cognitive closure and vaccine hesitancy

Abstract: Vaccination has become one of the most effective ways of controlling the spread of COVID-19. Consequently, revealing the evolutionary and cognitive antecedents of COVID-19 vaccine hesitancy and vaccination intention has become crucial. Drawing on the theory of behavioral immune system (BIS), we investigate whether perceived vulnerability to disease (PVD) is associated with vaccination intentions through the need for cognitive closure (NCC) and vaccine hesitancy. The data was collected from 525 adults from Turk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Specifically, individuals’ COVID-19 vaccination intention was higher when they had higher levels of pathogen disgust and higher levels of trust in government. Solak et al (2022) suggested that pathogen disgust is a fear of physical contamination and that individuals with high pathogen disgust are more sensitive to disease and contaminated environments, have greater uncertainty, and have a strong need for cognitive closure, so they want to make decisions as quickly as possible to eliminate this cognitive load at the expense of careful review of COVID-19 vaccines. Trust in the vaccine source/information can satisfy this need for cognitive closure and reduce uncertainty, thus making people more willing to vaccinate.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, individuals’ COVID-19 vaccination intention was higher when they had higher levels of pathogen disgust and higher levels of trust in government. Solak et al (2022) suggested that pathogen disgust is a fear of physical contamination and that individuals with high pathogen disgust are more sensitive to disease and contaminated environments, have greater uncertainty, and have a strong need for cognitive closure, so they want to make decisions as quickly as possible to eliminate this cognitive load at the expense of careful review of COVID-19 vaccines. Trust in the vaccine source/information can satisfy this need for cognitive closure and reduce uncertainty, thus making people more willing to vaccinate.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to vaccines, people are expected to have advanced health literacy to be able to make recommendations. Studies on this subject show that the doubts about the vaccine should be eliminated 39 , 40 and consumers need to receive positive feedback on the vaccines to be able to recommend them. Thus, previous studies on the subject support the hypotheses of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the behavioral intentions of consumers, it is necessary to first understand the impact of vaccines on health consumers, to be informed on the side effects of vaccines, and to identify the hesitations regarding vaccines. 39 , 40 Informing the public and managing the risks and crisis in health consumption is effective in increasing cognitive risk perception and reducing their emotional risk perception. 41 , 42 From this point of view, the health literacy levels of consumers can be said to shape their behavioral intentions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A possible explanation is that vaccines are administered in ways that in and by themselves are cues to contamination, such as puncturing the skin, and inhalation or ingestion of a foreign substance [3] . Early data on COVID-19 vaccines suggest that germ aversion predicts vaccination hesitancy during the current pandemic as well [ 13 , 25 ], even though there is a study reporting opposite findings [11] .…”
Section: Discussionmentioning
confidence: 99%